- ANALISIS YURIDIS TERHADAP PUBLIKASI PUTUSAN PENGADILAN ANAK YANG TIDAK MENGIKUTI PEDOMAN SURAT KEPUTUSAN KETUA MAHKAMAH AGUNG NOMOR 1-144/KMA/SK/I/2011 (STUDI PUTUSAN PENGADILAN NEGERI SERANG NOMOR 18/PID.SUS-ANAK/2021/PN.SRG). - Geovanni Ikram; Setiyono (Reformasi Hukum Trisakti, 2023)
Two 17-year-old children with the initials MRM and 16-year-old with the initials FAS proved legally and convincingly to have raped a 12-year-old girl with the initials SH. Juvenile offenders were arrested and tried in the Children's Court with the Decision of PN Serang Number 18/Pid.Sus-Anak/2021/PN Srg.  The problems of this research are, whether the publication of the decision of the Serang District Court Number 18/Pid.Sus-Child/2021 is appropriate, and what is legal consequences for the publication of the decision of the Serang District Court number 18/Pid.Sus-Child/2021/Srg.  The results of the research are that the decisions of the Serang District Court in cases of child and immoral crimes that are published without the disguise of identity as the guidelines in the Provision Letter Number 1-144/KMA/SK/I/2011106 are the ineffectiveness of the court apparatus that overshadows and decisions without obscuring the identity of the stated in the Decree of the Chief Justice of the Supreme Court Number 1-144/SK/KMA/2011 does not cancel the judge's decision, but will later become the responsibility of the Court Administrative Supervisory Board. Conclusion: decrees are recognized and have permanent legal force in General Courts, State Administrative Courts, Military Courts, and Religious Courts as stipulated in the Laws Forming Regulations. Recommendation: